2019
DOI: 10.5546/aap.2019.eng.397
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal pain and heart rate variability in preterm infants treated with surfactant: a pilot study

Abstract: Objective. We aimed to assess the pain perception of preterm infants treated with different surfactant administration techniques by using heart rate variability (HRV). Methods. Preterm infants who required surfactant therapy for RDS were randomized to INSURE or MIST groups. HRV analysis was performed by Newborn Infant Parasympathetic Evaluation monitor. HRV was recorded before, during and after surfactant administration. Pain assessment was determined by Premature Infant Pain Profile (PIPP) score. Results. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
2
1
Order By: Relevance
“…Other recent studies also used the NIPE index to adequately evaluate the balance between nociception and antinociception, assess parasympathetic activity, pain and pleasant stimuli, and validly record stress and pain in sedated children. 10,18,19 It must be noted that, however, considerable interindividual variations in NIPE, reflected by not-so small standard deviations in our study, may be an explanation for some inconsistencies among the results of different studies, particularly at small group sizes. NIPE response may furthermore depend on the strength of the nociceptive stimulus, since venous puncture (which elicited no significant change in NIPE values in our study) is obviously a weaker stimulus than laryngoscopy/intubation and skin incision (and may be further weakened by additional local anesthesia of the skin that children usually receive to facilitate puncture).…”
Section: Discussioncontrasting
confidence: 51%
“…Other recent studies also used the NIPE index to adequately evaluate the balance between nociception and antinociception, assess parasympathetic activity, pain and pleasant stimuli, and validly record stress and pain in sedated children. 10,18,19 It must be noted that, however, considerable interindividual variations in NIPE, reflected by not-so small standard deviations in our study, may be an explanation for some inconsistencies among the results of different studies, particularly at small group sizes. NIPE response may furthermore depend on the strength of the nociceptive stimulus, since venous puncture (which elicited no significant change in NIPE values in our study) is obviously a weaker stimulus than laryngoscopy/intubation and skin incision (and may be further weakened by additional local anesthesia of the skin that children usually receive to facilitate puncture).…”
Section: Discussioncontrasting
confidence: 51%
“…Cremillieux et al assessed responses in premature neonates and have presented results similar to ours: no correlation between changes of NIPEi and those measured using DAN and PIPP-R scales ( 31 ). Valencia-Ramos et al have found no NIPEi and COMFORT scale correlation in neonates during the nebulisation procedure; and nor did Okur et al, who used NIPEi and PIPP scale during surfactant administration in premature infants ( 32 , 33 ). On the contrary, Weissman et al have studied pain manifestation after HS using the Neonatal Facial Coding System and found a correlation with spectral analysis of heart rate variability ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A real-time HRV monitor could help understand when newborns need analgesic medications to withstand better invasive and noxious procedures or adjuvant neuroprotective therapies in case of HIEinfants who subsequently died due to HIE showed lower LF and higher HF- (Massaro et al, 2014), and it could also help choose better how to administer surfactant in case of respiratory distress syndrome-the NIPE index showed different values according to the technique used (Okur et al, 2019).…”
Section: Hrv As An Innovative Tool In Neonatal Decision-making Intervmentioning
confidence: 99%